2005
DOI: 10.1148/radiol.2372040837
|View full text |Cite
|
Sign up to set email alerts
|

The Lactating Breast: Contrast-enhanced MR Imaging of Normal Tissue and Cancer

Abstract: Normal lactating glands have increased density, high T2-weighted signal intensity, and rapid moderate contrast enhancement. Breast cancers are visible during lactation owing to their lower signal intensity and more intense initial contrast enhancement with early washout compared with normal breast tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 13 publications
1
48
1
2
Order By: Relevance
“…In addition to this, tissue uptake curves generated with values of T c on the order of 1 s result in errors well above 500% for v p (data not shown). Error is further increased when the AIF is mis-sampled, and it is particularly striking that when data are sampled at temporal resolutions greater than 9 s, which is typical of the temporal resolution currently employed in some studies (32)(33)(34)(35), errors for both K trans and v p are greatly increased.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, tissue uptake curves generated with values of T c on the order of 1 s result in errors well above 500% for v p (data not shown). Error is further increased when the AIF is mis-sampled, and it is particularly striking that when data are sampled at temporal resolutions greater than 9 s, which is typical of the temporal resolution currently employed in some studies (32)(33)(34)(35), errors for both K trans and v p are greatly increased.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of data on MRI features of PABC. Espinosa et al [7] reported MRI findings of five cases of breast carcinoma in lactating women. The MRI features of cancer in lactating breast tissue are similar to those of non-PABC cases and include homogeneously and heterogeneously enhancing masses (Figure 2c), mass with rim enhancement (Figure 3d), non-mass segmental enhancement and diffuse unilateral enhancement.…”
Section: Mrimentioning
confidence: 99%
“…Unlike non-lactating breast tissue (Figure 5a), lactating parenchyma (Figure 5b) shows rapid enhancement following intravenous administration of contrast material, followed by an early plateau of enhancement, a feature attributed to increased vascular permeability similar to that seen in invasive malignancy [7,8]. Rapid enhancement of lactating parenchyma may hamper MRI detection of malignancy (Figure 1c).…”
Section: Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…This can only be clarified by including pregnant patients in a study group and assessing their BPEs. There are only a few studies with limited sample size involving pregnant patients (25).…”
Section: Discussionmentioning
confidence: 99%